UNCOVERING IDEOLOGY AND NOBILITY IN THE MUNA FOLK TALE KARAMBAU KAINSEDODO: A CRITICAL DISCOURSE ANALYSIS OF HEREDITARY AUTHORITY AND TEXTUAL MEDIATION - Ela Martisa; Dahlia Husain (Indonesian EFL Journal, 2026)
This study examines the Muna folktale Karambau Kainsedodo as a cultural discourse that constructs hereditary authority, moral legitimacy, and noble identity. Previous studies on Indonesian folklore have mostly focused on moral values, themes, or cultural preservation, while limited attention has been given to how regional folktales reproduce ideology through linguistic choices and translation. This study aims to analyze how power relations and moral legitimacy are constructed in the tale, how ideological markers are mediated across Muna, Indonesian, and English versions, and how characters embody hereditary authority within Muna social ideology. This study used a qualitative design with Fairclough’s three-dimensional Critical Discourse Analysis, covering textual analysis, discursive practice, and social practice. The findings show that noble identity is constructed through titles, evaluative expressions, hospitality formulas, coercive commands, symbolic opposition, and ancestral invocation. Translation preserves the main narrative structure but reduces the cultural density of key terms such as kolaki. The folktale functions not only as a moral story but also as a discourse that legitimizes hereditary authority and demonstrates how translation mediates indigenous ideology. The findings may support culturally sensitive translation and the use of local folktales in English literature and EFL learning.